Deletion of 3 residues from the C-terminus of MCFD2 affects binding to ERGIC-53 and causes combined factor V and factor VIII deficiency - Nyfeler, Beat; Kamiya, Yukiko; Boehlen, Françoise; Yamamoto, Kazuo; Kato, Koichi; de Moerloose, Philippe; Hauri, Hans-Peter; Neerman-Arbez, Marguerite (Blood, 2008)
Combined factor V and factor VIII deficiency (F5F8D) is a rare, autosomal recessive coagulation disorder. F5F8D is genetically linked to mutations in the transmembrane lectin ERGIC-53 and its soluble interaction partner MCFD2. The ERGIC-53/MCFD2 protein complex functions as transport receptor of coagulation factors V and VIII by mediating their export from the endoplasmic reticulum (ER). Here, we studied a F5F8D patient who was found to be a compound heterozygote for 2 novel mutations in MCFD2: a large deletion of 8.4 kb eliminating the 5'UTR of the gene and a nonsense mutation resulting in the deletion of only 3 amino acids (DeltaSLQ) from the C-terminus of MCFD2. Biochemical and structural analysis of the DeltaSLQ mutant demonstrated impaired binding to ERGIC-53 due to modification of the 3-dimensional structure of MCFD2. Our results highlight the importance of the ERGIC-53/MCFD2 protein interaction for the efficient secretion of coagulation factors V and VIII.